PENGARUH KONSUMSI BAWANG BATAK TERHADAP KEPUTIHAN PADA WANITA USIA SUBUR DI DESA LAU RAKIT KECAMATAN STM HILIR KABUPATEN DELI SERDANG - Novita Br Ginting Munthe; Iskandar Markus Sembiring; Wilda Wahyuni Siregar (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
The health of female sex organs is something that needs special attention, especially in maintaining cleanliness at this time. In the vagina there is normal flora (microorganisms) which must be balanced. If this can not be done by women, it will cause disorders such as vaginal discharge. One well-known genus of plants that is widely used by the community is Batak (Allium). Most of this genus is used by the community as a spice in cooking and traditional medicine. Batak onion plants can inhibit the growth of microorganisms such as fungi that cause vaginal discharge. This study aims to determine the effect of the onion batak on Fertile Age Women (WUS) who experience vaginal discharge in Lau Rakit Village, STM Hilir District, Deli Serdang Regency, North Sumatra Province. The research method uses a